Gardner syndrome initially misdiagnosed as bilateral breast malignancy: a case report and literature review - Qian, Rong; Zhang, Guojin; Liu, Juan; Kong, Weifang (Frontiers in Oncology, 2026)
PurposeTo report a rare case of Gardner syndrome (GS) initially presenting with bilateral breast masses, emphasizing the diagnostic challenges of atypical manifestations and the importance of multidisciplinary collaboration.MethodsA retrospective analysis was conducted using clinical data, multimodal imaging (ultrasound, mammography, magnetic resonance imaging, and computed tomography), histopathological evaluation via core needle biopsy, and multidisciplinary team (MDT) consultation. Colonoscopy was performed to confirm systemic involvement.ResultsA 27-year-old woman presented with bilateral breast masses that were initially suspected to be malignant. Imaging revealed irregular spiculated lesions mimicking invasive carcinoma. Histopathological examination confirmed the presence of fibromatosis in both breasts and the right interpectoral region. Systemic evaluation revealed craniofacial osteomas, subcutaneous/muscular soft tissue tumors, left adrenal adenoma, and multiple colorectal polyps (superficial serrated adenomas). MDT review confirmed GS based on intestinal polyposis, osteomas, soft-tissue tumors, and histopathological criteria.ConclusionThis case underscores the critical role of multimodal imaging, histopathology, and MDT collaboration in clinical diagnosing GS with rare breast involvement. A systematic evaluation of extracolonic manifestations (e.g., adrenal adenomas) and the recognition of fibromatosis mimicking malignancy are essential for early diagnosis. Genetic evaluation and interdisciplinary management optimize the outcomes of complex hereditary syndromes.